Prolonged Codeine Administration Causes Degeneration of Myelinated Axons and Motor Dysfunction in Wistar Rats - Archibong VB; Usman IM; Lemuel AM (Dove Medical Press, 2022)
Victor Bassey Archibong,1- 3 Ibe Michael Usman,1 Ann Monima Lemuel1 1Department of Human Anatomy, Faculty of Basic Medical Sciences, Kampala International University, Bushenyi, Uganda; 2Department of Human Anatomy, Faculty of Basic Medical Sciences, University of Calabar, Calabar, Cross River State, Nigeria; 3Department of Clinical Biology, College of Medicine and Health Sciences, University of Rwanda, Kigali, RwandaCorrespondence: Ann Monima Lemuel, Tel +256 754031204, Email annexdot5@gmail.comPurpose: Over-the-counter (OTC) anti-cough medications which contain codeine (an opioid) are extensively available in Nigeria, and hence prone to overuse or abuse. The study aimed to understand the effects of oral codeine administration on the integrity of neurons of the cerebral cortex and cerebellum and its behavioral implications in male Wistar rats.Methods: Thirty adult male Wistar rats of comparable weights were obtained and randomly allocated into 5 groups: A, B, C, D, and E (n = 6). Drugs used for the study were ArchilinTM with codeine and dihydrocodeine 30mg. Group A served as control and was administered 0.5mL/kg of normal saline. Groups B and C were treated with 1mg/kg and 2mg/kg of dihydrocodeine, respectively; Group D and E received 2mL/kg and 4mL/kg of ArchilinTM codeine syrup, respectively. The ArchilinTM codeine syrup and dihydrocodeine solutions were administered to the animals based on their body weight, orally and daily with the aid of oropharyngeal tubes for 21 days. The experimental animals were subjected to neurobehavioral studies using beam walk and open field. At the end of the treatment period, the animals were anesthetized with ketamine-hydrochloride intraperitoneally. The brains were quickly dissected out, rinsed with normal saline, and tissue processed for myelin studies.Results: The beam walking and open field result revealed that prolonged codeine administration interfered with motor function in the experimental animals. Sections of the prefrontal cortex and cerebellum of rats given normal saline showed normal myelin sheaths, whereas animals in the treatment group showed degenerating myelin compared to the control.Conclusion: Prolonged consumption of prescription codeine causes degeneration of the myelin sheaths and this may affect the conduction of electrical impulses in myelinated axons thus resulting in motor function insufficiency.Keywords: codeine, substance abuse, dihydrocodeine, cough syrup, Wistar rats